Combined effects of viscous dissipation and temperature dependent thermal conductivity on MHD free convection flow with conduction and joule heating along a vertical flat plate - Nasrin, R.; Alim, M. A. (Journal of Naval Architecture and Marine Engineering, 2010)
Combined effects of viscous dissipation and temperature dependent thermal conductivity on MHD free convection flow with heat conduction and Joule heating along a vertical flat plate have been described in the present work. The governing boundary layer equations with associated boundary conditions for this phenomenon are converted to non-dimensional form using a suitable transformation. The resulting non-linear partial differential equations are then solved using the implicit finite difference method with Keller-box scheme. The numerical results in terms of the skin friction coefficient, the surface temperature, the velocity and the temperature profiles over the whole boundary layer are shown graphically for different values of the Prandtl number Pr, the magnetic parameter M, the thermal conductivity variation parameter γ, viscous dissipation parameter N and the Joule heating parameter J. Numerical results of the local skin friction co-efficient and the surface temperature profile for different values of N are presented in tabular form. Keywords: Joule heating; MHD; conduction; temperature dependent thermal conductivity; viscous dissipation; natural convection. DOI: 10.3329/jname.v5i2.2648 Journal of Naval Architecture and Marine Engineering 6(1)(2009) 30-40